Routine clinical practice in the periprocedural management of edoxaban therapy is associated with low risk of bleeding and thromboembolic complications: The prospective, observational, and multinational EMIT‐AF/VTE study. Issue 7 (14th May 2020) - Colonna, Paolo; von Heymann, Christian; Santamaria, Amparo; Saxena, Manish; Vanassche, Thomas; Wolpert, Diana; Laeis, Petra; Wilkins, Robert; Chen, Cathy; Unverdorben, Martin
Abstract: Background: Guidance for periprocedural anticoagulant management is mainly based on limited data from Phase III or observational studies and expert opinion. Hypothesis: EMIT‐AF/VTE was designed to document the risks of bleeding and thromboembolic events in more than 1000 patients on edoxaban undergoing diagnostic and therapeutic procedures in clinical practice. Methods: Routine care in a multinational multicenter, prospective observational study. Participants were adult patients with atrial fibrillation and/or venous thromboembolism treated with edoxaban for stroke prevention or for secondary prevention in venous thromboembolic disease, undergoing a wide range of diagnostic and therapeutic procedures. Edoxaban therapy was interrupted periprocedurally at the treating physician's discretion. Patients were evaluated from 5 days pre‐ until 30 days postprocedure. Primary outcome was the incidence of International Society on Thrombosis and Haemostasis defined major bleeding; secondary outcomes included incidence of clinically relevant non‐major bleeding, acute coronary syndrome, and acute thromboembolic events. Results: Outcomes and management are reported for the first procedures in 1155 unselected patients. Five cases of major bleeding (0.4%) and eight of clinically relevant non‐major bleeding (0.7%) were documented, five (38%) of which occurred outside the period of likely edoxaban effect (last edoxaban dose ≥3 days prior to bleeding). Five (0.4%) deaths from any cause, seven acute thromboembolic events (0.6%) including two cardiac deaths (0.2%) in six patients, and one acute coronary event (0.1%) occurred. Conclusions: The periprocedural bleeding and acute thromboembolic event risks for patients treated with edoxaban were low. This can help inform both clinical routine and guidelines for the periprocedural management of edoxaban.